METACOGNITIVE STRATEGIES FOR THE UNDERSTANDING AND PRODU - Inga Arias, Miguel Gerardo (2014)
This article presents a proposal of understanding and production of texts from a metacognitive perspective. It begins from a new text definition, framed inside textual linguistics, with the incidence of continuous text, its constitutive elements are hierarchy, coherence and cohesion. Then, there is a consideration about the mental processes that take place while reading, and therefore, also while writing. Finally, we present a model in which we applied the metacognitive reading in a text